2020
DOI: 10.1177/1708538120920500
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of bell-bottom technique compared to standard endovascular aneurysm repair

Abstract: Objective The bell-bottom technique is a widely used technique to treat aortoiliac aneurysms with preservation of the hypogastric arteries. The published data are scarce with conflicting results regarding the evolution. The aim of this study was to compare the outcomes of patients submitted to endovascular abdominal aortic aneurysm repair with standard technique (S-EVAR) versus bell-bottom technique. Methods This retrospective cohort study compared the outcomes of standard endovascular aneurysm repair (<16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Deery et al 17 reported graft limb occlusion in 2.3% of patients. Massière et al 11 reported 2 (1%) cases of occlusion within the perioperative period. Sirignano et al 12 noted that out of the 20 reinterventions needed at some point during the 35 months follow-up, 7 were due to endograft limb occlusion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Deery et al 17 reported graft limb occlusion in 2.3% of patients. Massière et al 11 reported 2 (1%) cases of occlusion within the perioperative period. Sirignano et al 12 noted that out of the 20 reinterventions needed at some point during the 35 months follow-up, 7 were due to endograft limb occlusion.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout long-term follow-up, the freedom from type Ia endoleak was reported in 99% and 97% at 1 and 5 years follow-up, respectively. Massière et al 11 reported on long-term prevalence of type I endoleak and noted 2 cases (1%) of type Ia endoleak and 5 cases (2%) of type Ib endoleak. Sirignano et al 12 reported 6 cases of type Ia endoleak (2%), 3 type Ib endoleak (1%), 7 type II endoleak (2%), and 1 type III endoleak (0.3%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To mitigate these complications, preservation strategies for the IIA, such as the bell-bottom technique (BBT) and the iliac branch device (IBD), have been proposed [7,8]. However, the BBT has limitations, as landing a flared iliac limb graft onto the dilatation of a CIA may result in the secondary dilatation of the distal landing zone over time, leading to a type 1B endoleak [9].…”
Section: Introductionmentioning
confidence: 99%